Analisis Literasi Informasi Bencana melalui Media Sosial Instagram di SMA Negeri Kota Samarinda - Tyas Utami Juliantari; Mei Vita Romadon Ningrum; Rahmadi; Najma Nur Mawaddah (Mataram University, 2026)
Samarinda City is one of the areas with a high level of disaster risk, making this condition an important issue to investigate. In the current digital era, Instagram has developed into a major social media platform used by adolescents, including high school students, to access disaster-related information. However, relatively few studies have quantitatively examined the level of disaster information literacy among high school students through Instagram in preparing for potential disasters. This study aims to analyze the level of disaster information literacy through Instagram among high school students in Samarinda City. This research employed a quantitative descriptive approach, with the sample consisting of students from three public senior high schools in Samarinda City: MAN 2 Samarinda, SMAN 5 Samarinda, and SMAN 14 Samarinda. The samples were selected using purposive sampling, involving a total of 200 students. Data were collected through questionnaires, documentation, and interviews. Data analysis involved instrument testing, including validity and reliability tests, followed by descriptive analysis. The results showed that the level of disaster information literacy through Instagram among public senior high school students in Samarinda City was categorized as high, with a score of 78.37.